Antimicrobial Susceptibility Profile of Pathogenic and Commensal Bacteria Recovered from Cattle and Goat Farms - Winnie Mukuna; Tobenna Aniume; Bharat Pokharel; Collins Khwatenge; Ashesh Basnet; Agnes Kilonzo-Nthenge (MDPI AG, 2023)
The use of antibiotics in food animals results to antimicrobial resistant bacteria that complicates the ability to treat infections. The purpose of this study was to investigate the prevalence of pathogenic and commensal bacteria in soil, water, manure, and milk from cattle and goat farms. A total of 285 environmental and 81 milk samples were analyzed for Enterobacteriaceae by using biochemical and PCR techniques. Susceptibility to antibiotics was determined by the Kirby-Bauer disk diffusion technique. A total of 15 different Enterobacteriaceae species were identified from goat and cattle farms. Manure had significantly higher (p < 0.05) Enterobacteriaceae (52.0%) than soil (37.2%), trough water (5.4%), and runoff water (5.4%). There was a significant difference (p < 0.05) in Enterobacteriaceae in goat milk (53.9%) and cow milk (46.2%). Enterobacteriaceae from environment showed 100% resistance to novobiocin, erythromycin, and vancomycin E. coli O157:H7, Salmonella spp., Enterococcus spp., and Listeria monocytogenes displayed three, five, six, and ten. AMR patterns, respectively. NOV-TET-ERY-VAN was the most common phenotype observed in all isolates. Our study suggest that cattle and goat farms are reservoirs of multidrug-resistant bacteria. Food animal producers should be informed on the prudent use of antimicrobials, good agricultural practices, and biosecurity measures.